القیم الاجتماعیة السائدة عند تلامذة الصف الاول الابتدائي - أ.د. حسین نوري الیاسري أ.م. فوزیة عودة الكبیسي (College of Education for Women, 2019)
The research aims at: 1 - Detection of the degree of social values (truthfulness, honesty, cooperation) of the primary first class students who compose members of the research sample in general. 2 - Are there significant differences at the level (0,05%) between the average degree of members of the research sample in the values (truthfulness, honesty, cooperation) among students enrolled and not enrolled in kindergarten and in general. 3 - Are there significant differences at the level (0,05%) between the mean scores of individuals in the sample values (truthfulness, honesty, cooperation) in the light of two variables: A - Gender (male / female), b - enrolled and not enrolled in kindergarten. Having in mind that the researchers followed the descriptive approach in the analysis of their results which they reached through the search tool, which was subject to the procedures of the construction methodology accepted by such researches. The research shows the following results: The average degrees of members of the research sample is higher than the average premise. The results of this research also indicate that there are significant differences between enrolled and not enrolled students in the values of truthfulness and cooperation in favour of students enrolled in kindergarten. These results don't indicate the existence of significant differences between enrolled and not enrolled in the value of honesty. With regard to the third objective, the research results indicated that there were significant differences between males and females in the value of truthfulness in favor of females enrolled. With regard to the value of honesty, in the light of variables (Gender, enrollment and not enrollment in the kindergarten) it was in favor of females. With regard to whether or not to attend kindergarten, the results show no significant differences between enrolled and not enrolled in kindergarten. With regard to the value of cooperation, the results of research show that there are no significant differences between the sexes. With regard to enrollment and non-enrollment, the research results were for the benefit of children enrolled in kindergarten. The researchers and in the light of the results also present certain recommendations.